Tobacco Use Disorder: A Family Disease. Issue 3 (May 2016) - DiFranza, Joseph R.; Bhuvaneswar, Chaya; Jolicoeur, Denise; Tanski, Susanne E.; Winickoff, Jonathan
Abstract : This clinical case presentation discusses a family in which 3 generations are affected by tobacco. The discussants discuss approaches to be taken to minimize the exposure of an infant to tobacco smoke from older relatives, behavioral and pharmacological approaches to assist smoking cessation, and concerns regarding electronic cigarettes.